PENGARUH STRATEGI DIVERSIFIKASI, INTELLECTUAL CAPITAL DAN KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA PERUSAHAAN DI INDONESIA - Muthia Safira Ariani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2019)
As an effort to fulfill the demands of the community needs and improving corporate performance, the implementation of various strategies and good corporate management are believed to be a very important steps. The purpose of this study was to examine the effect of diversification strategies, intellectual capital and company characteristics to the firm performance in Indonesia. The sample used are consumer goods sub-sector of manufacturing companies listed in the Indonesia Stock Exchange from 2015 to 2017 period. The results prove that there are negative influences of diversification and leverage, and the positive influences of intellectual capital and firm size to the firm performance.